Pemanfaatan Teknologi Berbasis Android sebagai Media Pembelajaran bagi Guru SMA Negeri - Endang Sri Utami; Erni Mariana; Novita Novita; Kusuma Wardany; Ayang Kinasih (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2022)
In an effort to avoid the Covid-19 pandemic, the government has issued a policy that schools ask their students to study at home. Starting March 16, 2020, the school will practice online student education procedures. The online education system (on the network) is an education system without direct face-to-face between teachers and students but is carried out online using the internet network. Teachers are obliged to allow teaching and learning activities to continue, even though students are at home. The solution, teachers are required to be able to design educational media as an innovation by using online media (online). State Senior High Schools also practice the online education model due to the diversity of teacher competency levels in conducting online education so assistance in the application of online education is needed. Lecturers who have the Tri Dharma of higher education, one of which is a dedication to the community, can function and assist in online education. Assistance is carried out by carrying out socialization and training and followed by assistance in the application of online education. The media used is Google Classroom, as well as making educational videos uploaded on YouTube. The result of the dedication of these residents is that teachers already have online classes and can carry out online class management and online classroom care.